Dual-Polymer Drops, Contact Lens Comfort, and Lid Wiper Epitheliopathy. Issue 8 (August 2016) - Nichols, Jason J.; Lievens, Christopher W.; Bloomenstein, Marc R.; Liu, Haixia; Simmons, Peter; Vehige, Joseph
ABSTRACT: Purpose: This study compared a new contact lens rewetting drop containing both carboxymethylcellulose and hyaluronic acid (CMC-HA) with a standard drop containing carboxymethylcellulose only (CMC). Symptoms of discomfort typical in lens wear and lid wiper epitheliopathy (LWE) were assessed over a 3-month period in a diverse sample of contact lens wearers. Methods: Adapted daily-wear contact lens subjects using hydrogel, silicone hydrogel, or rigid gas permeable lenses were enrolled in this prospective, randomized, double-masked, parallel-group, 90-day study conducted at 15 clinical sites. Subjects were randomized 2:1 to CMC-HA (n = 244) or CMC alone (n = 121) with dosage at least four times per day, along with their habitual lens care system. At baseline and at days 7, 30, 60, and 90, subject-completed questionnaires, bulbar conjunctival staining, LWE, contact lens distance visual acuity (CLDVA), and standard safety measures were assessed. Results: At day 90, CMC-HA performed significantly better than CMC in ocular symptoms including dryness throughout the day (p = 0.006), and burning/stinging throughout the day (p = 0.02) and at the end of the day (p < 0.001). CMC-HA also performed numerically better for dryness at the end of day (p = 0.06). LWE staining was improved in the CMC-HA group at day 90 whereas it increased slightly in the CMC alone group, with a significant between-group difference (p = 0.009). CMC-HA also demonstrated greater reduction in conjunctival staining compared with CMC alone at day 90 (p = 0.08). No differences in CLDVA, contact lens wear time, acceptability, and product use were observed, and safety outcomes were similar between groups. Conclusions: The addition of HA to a standard CMC rewetting drop improves clinical performance. In this comparison of rewetting drop efficacy in contact lens wearers, LWE was a useful clinical sign for differentiating clinical performance.